Depletion of U3 small nucleolar RNA inhibits cleavage in the 5' external transcribed spacer of yeast pre-ribosomal RNA and impairs formation of 18S ribosomal RNA. - Hughes, J M (EMBO J, 1991)
Multiple processing events are required to convert a single eukaryotic pre-ribosomal RNA (pre-rRNA) into mature 18S (small subunit), 5.8S and 25-28S (large subunit) rRNAs. We have asked whether U3 small nucleolar RNA is required for pre-rRNA processing in vivo by depleting Saccharomyces cerevisiae of U3 by conditional repression of U3 synthesis. The resulting pattern of accumulation and depletion of specific pre-rRNAs indicates that U3 is required for multiple events leading to the maturation of 18S rRNA. These include an initial cleavage within the 5' external transcribed spacer, resembling the U3 dependent initial processing event of mammalian pre-rRNA. Formation of large subunit rRNAs is unaffected by U3 depletion. The similarity between the effects of U3 depletion and depletion of U14 small nucleolar RNA and the nucleolar protein fibrillarin (NOP1) suggests that these could be components of a single highly conserved processing complex. IMAGES: